Achalasia Cardia - Case Report - Islam, Md Baharul; Rahman, Md Khalilur; Sarker, Abul Kashem (TAJ: Journal of Teachers Association, 2011)
A 45 years old man was admitted in the surgery unit-ll at Rajshahi Medical College Hospital with the complaints of prolonged dysphagia and regurgitation of food and saliva. The patient had some weight loss but no anorexia, Barium swallow oesophagus showed marked dilatation of oesophagus with regular tapering of its lower end. The patient was diagnosed as achalasia cardia and underwent oesophago-cardio-myotomy operation. The patient relieved from his symptoms. He was followed up for 1 year and found healthy. DOI: http://dx.doi.org/10.3329/taj.v14i2.8393 TAJ 2001; 14(2): 85-87